THE DIALECTIC OF DIVINE TRANSCENDENCE AND IMMANENCE IN THE LORD’S PRAYER (MATT. 6:9-13): A THEOLOGICAL-EXEGETICAL STUDY - Tan Markus Setiadi Wahyu; Simon Stefanus Baitanu (Diegesis : Jurnal Teologi, 2026)
This article examines how the Lord’s Prayer (Matt. 6:9-13) articulates the relationship between divine transcendence and immanence within Jesus’ instruction on prayer. While major Matthean and Lord’s Prayer provide extensive exegetical, literary, and theological discussions of the text, the interplay of transcendence and immanence is often treated implicitly or dispersed across broader themes (such as kingdom, discipleship, ethics, and eschatology) rather than analyzed as an integrated theological pattern within the prayer’s structure. Addressing this gap, the study employs qualitative research through close exegetical reading of Matthew 6:9-13 alongside systematic-theological analysis. The analysis suggests that the opening address, “Our Father in heaven,” functions to hold together God’s nearness (“Father”) and otherness (“in heaven”) as a framing tension for the petitions that follow. The first triad of petitions (“hallowed be your name,” “your kingdom come,” “your will be done”) is read as primarily oriented toward God’s sovereign initiative and holiness, whereas the second triad (“give us today our daily bread,” “do not bring us into temptation,” “deliver us from the evil one”) foregrounds divine provision, forgiveness, and protection in the lived experience of the praying community. Furthermore, the prayer’s theological coherence is interpreted in relation to Jesus’ teaching authority in Matthew, where Jesus mediates the knowledge of God and shapes the disciples’ address to God. The article argues that reading the Lord’s Prayer through the transcendence–immanence lens clarifies its internal logic and offers a constructive framework for describing divine-human relationality in Matthean prayer practice.